Dissociative electron attachment to gold(I)-based compounds: 4,5-dichloro-1,3-diethyl-imidazolylidene trifluoromethyl gold(I) - Pintea, Maria; Mason, Nigel; Peiró-Franch, Anna; Clark, Ewan; Samanta, Kushal; Glessi, Cristiano; Schmidtke, Inga Lena; Luxford, Thomas (Frontiers in Chemistry, 2023)
With the use of proton-NMR and powder XRD (XRPD) studies, the suitability of specific Au focused electron beam induced deposition (FEBID) precursors has been investigated to low electron energy, structure, excited states and resonances, structural crystal modifications, flexibility, and vaporization level. Uniquely designed precursor to meet the needs of focused electron beam induced deposition at the nanostructure level, the 4,5-dichloro – 1,3-diethyl – imidazolylidene trifluoromethyl gold(i) (Fig 1) is a compound that proves its capability to create high purity structures, and its growing importance between other AuImx and AuClnB (where x, n are the number of radicals, B = CH, CH3 or Br) compounds in the radiation cancer therapy increases the efforts to design more suitable bonds in processes of SEM (Scanning Electron Microscopy) deposition and in gas-phase studies. The investigation done to its powder shape using the XRPD XPERT3 Panalytical diffractometer based on CoKα lines shows changes to its structure with temperature, level of vacuum, and light; the sensitivity of this compound making it highly interesting to the radiation research in particular. Used for FEBID, through its smaller number of C, H and O atoms has lower levels of C contamination in the structures and on the surface, but it replaces these bonds with C – Cl and C – N bonds that have a lower bond breaking energy, but still needing an extra purification step in the deposition process, whether is H2O, O2 or H jets.